RETHINKING DENSITY IN URBAN PLANNING: POLICY DIRECTIONS IN THE POST-COVID-19 ERA IN MALAYSIA - Lim, Seng Boon; Abdul Malek, Jalaluddin; Abdul Rashid, Mohd Fadzil; Chee Kong, Yong (PLANNING MALAYSIA, 2021)
Since the ‘Coronavirus Disease 2019’ (COVID-19) struck the world and Malaysia, the general attention of the media and leaders has been focused on the high population density areas that have high infection rates and deaths. This article aims to rethink population density in urban development policy, thus providing development for policy direction in the post-COVID-19 era in Malaysia. The available national development planning policies in Malaysia, i.e., the National Physical Plan and the National Urbanisation Policy, and scholarly articles related to the population density topic were investigated through a scoping literature review and a keyword analysis. The findings showed mixed results in terms of the relationship between dense areas causing higher rates of COVID-19 infection and death rates. This article argues that policies related to spatial urban planning should continuously advocate dense city planning in considering how to achieve economic, social, and environmental sustainability and human quality of life. To this extent, this article contributes to the densification topic in spatial urban planning policies in terms of their application in the post-COVID-19 era, which needs urgent direction and clarification.